Reconstruction of Ankle and Heel Defects with Peroneal Artery Perforator-Based Pedicled Flaps - Ahn, Deok Ki (Arch Plast Surg, 2015)
BACKGROUND: The reconstruction of ankle and heel defects remains a significant problem for plastic surgeons. The following options exist for reconstructing such defects: local random flaps, reverse flow island flaps, and free flaps. However, each of these methods has certain drawbacks. Peroneal artery perforators have many advantages; in particular, they are predictable and reliable for ankle and heel reconstructions. In this study, we report our clinical experience with peroneal artery perforator-based pedicled flaps in ankle and heel reconstructions. METHODS: From July 2005 to October 2012, 12 patients underwent the reconstruction of soft tissue defects in the ankle and heel using a peroneal artery perforator-based pedicled flap. These 12 cases were classified according to the anatomical area involved. The cause of the wound, comorbidities, flap size, operative results, and complications were analyzed through retrospective chart review. RESULTS: The mean age of the patients was 52.4 years. The size of the flaps ranged from 5×4 to 20×8 cm(2). The defects were classified into two groups based on whether they occurred in the Achilles tendon (n=9) or heel pad (n=3). In all 12 patients, complete flap survival was achieved without significant complications; however, two patients experienced minor wound dehiscence. Nevertheless, these wounds healed in response to subsequent debridement and conservative management. No patient had any functional deficits of the lower extremities. CONCLUSIONS: Peroneal artery perforator-based pedicled flaps were found to be a useful option for the reconstruction of soft tissue defects of the ankle and heel.